Postpartum uterine prolapse and its relation to hypocalcaemia in local ewes in Basrah province - Fahid, Tahir A. (The Iraqi Journal of Veterinary Medicine, 2014)
This study was performed on a 10 of local ewes during 24 hours after lambing. Five of the ewes suffering from uterine prolapse (treated group), and other five ewes didn’t show uterine prolapse (control group). The study shows a relation between the calcium serum level and incidence of uterine prolapse after lambing. The result of study indicated that, a low level of calcium in the serum of treated group (2.29±0.33 mg/dl) as compared with the level of the calcium in the serum of the control group (6.52±0.30). The results indicated that the calcium deficiency (hypocalcaemia) in the late stage of pregnancy and at the lambing time may lead to uterine prolapse in ewes.